A STUDY ON SYNTACTIC AND PRAGMATIC FEATURES OF THANK-GIVINGS IN ENGLISH AND VIETNAMESE - Ph.D Lê Tấn Thi (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
- This study aims to find out differences and similarities in ways of thank-givings; the affect of Social and Cultural behaviors in thanking in the two languages: English and Vietnamese.